Spheroids of Bladder Smooth Muscle Cells for Bladder Tissue Engineering. (11th November 2021) - Gerwinn, Tim; Salemi, Souzan; Krattiger, Lisa; Eberli, Daniel; Horst, Maya
Abstract : Cell-based tissue engineering (TE) has been proposed to improve treatment outcomes in end-stage bladder disease, but TE approaches with 2D smooth muscle cell (SMC) culture have so far been unsuccessful. Here, we report the development of primary bladder-derived 3D SMC spheroids that outperform 2D SMC cultures in differentiation, maturation, and extracellular matrix (ECM) production. Bladder SMC spheroids were compared with 2D cultures using live-dead staining, qRT-PCR, immunofluorescence, and immunoblotting to investigate culture conditions, contractile phenotype, and ECM deposition. The SMC spheroids were viable for up to 14 days and differentiated rather than proliferating. Spheroids predominantly expressed the late myogenic differentiation marker MyH11, whereas 2D SMC expressed more of the general SMC differentiation marker α -SMA and less MyH11. Furthermore, the expression of bladder wall-specific ECM proteins in SMC spheroids was markedly higher. This first establishment and analysis of primary bladder SMC spheroids are particularly promising for TE because differentiated SMCs and ECM deposition are a prerequisite to building a functional bladder wall substitute. We were able to confirm that SMC spheroids are promising building blocks for studying detrusor regeneration in detail and may provide improved function and regenerative potential, contributing to taking bladder TE a significant step forward.